Safe storage - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Manual on the prevention of postharvest grain losses by J Gwinner, R Hamisch and O Muck 1990 294pp Published by GTZ, Postfach 5180 D-6236 Eschborn, GERMANY